COMUNICAÇÃO E LICENCIAMENTO AMBIENTAL: ESTUDO DE CASO DO RODOANEL MÁRIO COVAS - TRECHO LESTE - PASCHOIN, CRISTIANE HOLANDA MORAES (2016)
The Social Communication programs in road projects are planned in most environmental studies when there is the need to carry out environmental licensing and the participation of social groups in the enterprise. These programs take the preventive nature of the project and are usually instituted to ensure environmental quality, seeking a balance between economic and social development and environmental conservation. In this sense, the implementation of road projects generates impacts on the environment and the whole society, because, in addition to altering the physical characteristics of the region, they significantly interfere in people's daily lives. This study aims to analyze the requirements of the Social Communication Program, the Basic Plan Environmental Mario Covas Ring Road - Excerpt East, as well as be about underlying issues, such as drawing a rodoviarismo panorama in Brazil; make a historical environmental licensing; discuss the importance of business and the media in the alignment of social responsibility; and finally understand the communication processes and social interaction during the construction of the highway, assessing to what extent the media plays a mediating role in the development of relations with the affected social groups. For this, as a case study, the Mario Covas Ring Road - Eastern Section was used as reference and descriptive research and field research to evaluate this relationship with the affected communities. As a result of this research, we found that the Social Communication Program during the implementation of the project was insufficient, as it did not fulfill its initial objectives, and did not advance as a mediator in relations.